Fatigue in Chinese Patients With Amyotrophic Lateral Sclerosis: Associated Factors and Impact on Quality of Life - An, Ran; Li, Cheng; Li, Xin; Wu, Yuan; He, Xianghua; Ai, Shaolong; Xu, Yanming; He, Chengqi (Frontiers in Neurology, 2022)
Objectives: Fatigue was considered a common symptom in amyotrophic lateral sclerosis (ALS). Previous studies about the impact of fatigue on quality of life (QOL) in ALS patients was limited and inconsistent. Besides, systematical investigation of fatigue in Chinese patients with ALS was lacking. Therefore, the aim of our study was to comprehensively evaluate the frequency and associated factors of fatigue, as well as impact on QoL in Chinese ALS patients. Participants and Methods: Probable and definitive ALS patients and age- and sex-matched healthy controls were consecutively recruited. Disease severity, sleep quality, sleepiness, fatigue, anxiety, depression was evaluated by ALS Functional Rating Scale-revised (ALSFRS-R) and ALS severity scale (ALSSS), Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness Scale (ESS), Fatigue Severity Scale (FSS), Hamilton Anxiety Rating Scale (HARS) and Hamilton Depression Rating Scale (HDRS). McGill Quality of Life Questionnaire was used to measure QoL. Results: Fatigue was significantly more frequent in patients with ALS than in controls (32.6% vs17.7%, p=0.001). ALS patients with fatigue scored lower on ALSFRS-R, ALSSS (lower extremity+upper extremity, LE+UE), total ALSSS, higher in HARS, HDRS, PSQI, ESS scores and a poorer QoL. Daytime dysfunction and ALSSS(LE+UE) score were associated with a higher risk of fatigue. ALSSS(LE+UE), FSS, age, HARS and HDRS score were significantly associated with various aspects of QoL. Conclusion: Our study was the first study to characterize fatigue in Chinese ALS patients, finding daytime dysfunction and lower ALSSS(LE+UE) as risk factors for fatigue. Also, we firstly identified the adverse effects of fatigue intensity on psychological domain of QoL.